Effect of Maternal HIV Infection on Infant Development and Outcomes - Ruck, Candice E.; Smolen, Kinga K. (Frontiers in Virology, 2022)
Early life represents a period of profound immunological development and heightened susceptibility to infectious disease. The developmental trajectory over this period is influenced by a number of factors, including gestational age, mode of delivery, mode of feeding, microbiome development, and environmental exposures. There are also several maternal factors that have been shown to have a negative effect on both immune development and clinical outcomes, including maternal infection and inflammation. Studies have associated maternal HIV infections with an increase in infectious morbidity and mortality and decreased growth measures among their HIV-exposed uninfected (HEU) offspring. Among HEU infants, socioeconomic factors, maternal nutrition, maternal viral load, and maternal inflammation have also all been associated with impaired infant immune status and clinical outcomes. However, the mechanisms underlying these observations have not been elucidated and, apart from measures of disease severity, few studies thus far have undertaken in-depth assessments of maternal health status or immune function during gestation and how these influence developmental outcomes in their infants. The lack of a mechanistic understanding of how these gestational influences affect infant outcomes inhibits the ability to design and implement effective interventions. This review describes the current state of research into these mechanisms and highlights areas for future study include; how HIV infection causes the inflammatory trajectory to deviate from normal gestation, the mechanism(s) by which in utero exposure to maternal inflammation influences infant immune development and clinical outcomes, the role of socioeconomic factors as an inducer of maternal stress and inflammation, and maternal nutrition during gestation.